Evaluating landscape metrics for characterising hydrological response to storm events in urbanised catchments. Issue 3 (15th March 2020) - Miller, James D.; Stewart, Elisabeth; Hess, Tim; Brewer, Tim
ABSTRACT: Hydrological response of an urban catchment to storm events is determined by a number of factors including the degree of urbanisation and distribution and connectivity of urbanised surfaces. Therefore, the ability of spatially averaged catchment descriptors to characterise storm response is limited. Landscape metrics, widely used in ecology to quantify landscape structure, are employed to quantify urban land-cover patterns across a rural-urban gradient of catchments and attribute hydrological response. Attribution of all response metrics, except peak flow, is improved by combining lumped catchment descriptors with spatially explicit landscape metrics. Those representing connectedness and shape of suburban and natural greenspace improve characterisation of percentage runoff and storm runoff. Connectivity and location of urban surfaces are more important than impervious area alone for attribution of timing, validating findings from distributed hydrological modelling studies. Findings suggest potential improvements in attribution of storm runoff in ungauged urban catchments using landscape metrics.